(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The main provisions of forming media competence of a secondary linguistic personality – a new pedagogical phenomenon – are identified. In the course of analyzing the experience of well-known domestic and foreign teachers in the field of media education and teaching a foreign language, the general trends of the described process are studied, pedagogical principles are formulated aimed at developing the media competence of a secondary linguistic personality and contributing to its successful formation.